2008
DOI: 10.1103/physreve.78.056202
|View full text |Cite
|
Sign up to set email alerts
|

Trace formula for dielectric cavities: General properties

Abstract: The construction of the trace formula for open dielectric cavities is examined in detail. Using the Krein formula it is shown that the sum over cavity resonances can be written as a sum over classical periodic orbits for the motion inside the cavity. The contribution of each periodic orbit is the product of the two factors. The first is the same as in the standard trace formula and the second is connected with the product of reflection coefficients for all points of reflection with the cavity boundary. Two asy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(96 citation statements)
references
References 44 publications
(108 reference statements)
4
91
0
1
Order By: Relevance
“…Therefore, "no mode can disappear to infinity" along the imaginary direction in complex frequency space. This implies that the total number of internal modes of a dielectric cavity fulfills the conventional k 2 law as it was pointed out by Bogomolny et al (2008). This, however, is not in contradiction with the fractal Weyl law which applies to the long-lived modes within the set of internal modes.…”
Section: Level Statisticsmentioning
confidence: 78%
See 2 more Smart Citations
“…Therefore, "no mode can disappear to infinity" along the imaginary direction in complex frequency space. This implies that the total number of internal modes of a dielectric cavity fulfills the conventional k 2 law as it was pointed out by Bogomolny et al (2008). This, however, is not in contradiction with the fractal Weyl law which applies to the long-lived modes within the set of internal modes.…”
Section: Level Statisticsmentioning
confidence: 78%
“…However, the authors emphasized the need of higher-order corrections of the trace formula and showed that the application of curvature corrections to the Fresnel reflection coefficients improves the agreement (Bittner et al, 2012b). Bogomolny et al (2008) have shown that higher-order corrections lead to a small shift of the peak positions in the length spectrum which can be interpreted as an analogue to the Goos-Hänchen shift. Hales et al (2011) extended the trace formula to the case of a dielectric disk with a point scatterer.…”
Section: Semiclassical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The outer resonances constitute extremely broad background in the density of states because of their quite high leakage and they should be take into account in the study of the trace formula in open cavity [22,33].…”
Section: Discussionmentioning
confidence: 99%
“…Although the results presented are for the TM case, there is generally no lower limit of imaginary values because the mode coupling to the environment is not intrinsically limited. Rather, the coupling between internal and external (or outer or shape [49][50][51][52]) resonances, i.e. modes localized inside and outside the cavity respectively, causes as broad distribution of imaginary parts.…”
Section: Ray-wave Correspondence In Coupled Optical Microdisksmentioning
confidence: 99%